EXPLORING SELF-DETERMINATION AND EDUCATIONAL IDEALS IN PURSUIT OF HAPPINESS BY GABRIEL MUCCINO - Yuanita, Tanty; Said, Mashadi; Saragih, Gustaman (INFERENCE: Journal of English Language Teaching, 2024)
The aim of this research is to analyze self-determination and educational ideals in "Pursuit of Happyness" by Gabriel Muccino. The research adopts a qualitative approach, employing a descriptive qualitative method to analyze data from the movie. The technique involves examining the story, and dialogue that contains self-determination and moral values. Deci and Ryan's theory (2012) is utilized for examining self-determination, while Morska's theory (2018) is applied to educational values. The data analysis in "Pursuit of Happyness" reveals a total of 15 dialogues describing self-determination. Autonomy comprises the highest percentage with 6 dialogues (40,0%), followed by relatedness with 5 dialogues (33,3%), and competence with 4 dialogues (26,7%). Additionally, the analysis of dialogues identifies a total of 18 dialogues related to educational ideals in the movie. Focus values have the highest percentage, encompassing 10 dialogues (55,6%), followed by aspirational values with 5 dialogues (27,8%), and foundation values with 3 dialogues (16,7%).